Питання національної ідентичності в прізвиськах (на матеріалі неофіційних іменувань жителів Західного Полісся) - Шульська, Наталія Миколаївна; Shulska, Nataliia M. (Univerzity Karlovy v Praze, 2011)
In the article the individual and family nicknames of inhabitants of Western Polissya are analysed. On material of a plenty of collected by an author unofficial antroponimiv in 130 villages of the Volyn and Rivne regions of Ukraine traced specific of national identity in nicknames. For the detailed description of nicknames the most reprezentative motivation groups are selected. The analysed nicknames are distributed after the national belonging, external signs, internal features, unusual event in the life of transmitter and other reasons of nomination, at which complete or partly present element of national identity. Nicknames of inhabitants of Western Polissya are analysed in a dialectal aspect with saving of all specific lines of manner of speaking and ethnography of the explored territory. Near every fixed nickname a settlement in which it widening and where was written down by an author from local inhabitants is given.
The guestions of national identity in nicknames (based on informal names of inhabitants of Western Polissya)
Keywords: прізвисько; Західне Полісся; неофіційна антропонімія; національна ідентичність